Perancangan Alat Monitoring Ketinggian Air (Water Level) Berbasis Iot Pt. Usaha Gedung Mandiri - Dicky Resta Kusuma; Munawaroh (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
PT. Usaha Gedung Mandiri Building Business is a company engaged in building management. The company has water pumping activities for building needs at PT. Independent Building Business. How to meet these needs, PT. The Mandiri Building business does this by using an alarm, this still has shortcomings in pumping water as needed by giving a negative impact on the frequent errors of water pumping alarms. Based on the existing problems, PT. The Mandiri Building Business requires, implements, and adds technology to support needs and reduce negative impacts by adding Internet Of Things (IOT) to carry out existing activities at PT. Independent Building Business. As a company that has been trusted by several vendors who have collaborated with PT. Mandiri Building Business, the addition of IoT-based technology is expected to help interested parties and reduce the negative impact that exists on current problems at PT. Independent Building Business